2009
DOI: 10.3163/1536-5050.97.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Status of open access in the biomedical field in 2005

Abstract: In 2005, OA in the biomedical field was achieved under an umbrella of existing scholarly communication systems. Typically, OA articles were published as part of subscription journals published by scholarly societies. OA journals published by BioMed Central contributed to a small portion of all OA articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 7 publications
1
43
0
3
Order By: Relevance
“…Este estudio constituye el primero hasta la fecha en analizar la relación entre la publicación en abierto y el impacto, en términos de citación, de los artículos científicos relacionados con la medicina intensiva. El 27% de los artículos del ámbito biomédico publicados en el año 2005 fueron artículos con acceso abierto 21 , lo que concuerda con el 24% de los artículos con acceso abierto presentes en nuestro estudio, publicados en el año 2008, y representa cifras muy superiores al 6% obtenido por otro estudio 22 , también en el ámbito médico. Estos resultados podrían interpretarse como una buena adherencia al acceso abierto en el ámbito de la medicina intensiva.…”
Section: Discussionunclassified
“…Este estudio constituye el primero hasta la fecha en analizar la relación entre la publicación en abierto y el impacto, en términos de citación, de los artículos científicos relacionados con la medicina intensiva. El 27% de los artículos del ámbito biomédico publicados en el año 2005 fueron artículos con acceso abierto 21 , lo que concuerda con el 24% de los artículos con acceso abierto presentes en nuestro estudio, publicados en el año 2008, y representa cifras muy superiores al 6% obtenido por otro estudio 22 , también en el ámbito médico. Estos resultados podrían interpretarse como una buena adherencia al acceso abierto en el ámbito de la medicina intensiva.…”
Section: Discussionunclassified
“…16 If the figures of the present study are interpreted as meaning that it takes eight years to achieve a similar proportion (26.89%) of freely accessible papers, then the logical conclusion is that Spanish papers are less accessible than the average, taking into account that the 19.4% of the general study by Björk was achieved only a few months after publication. However, if the share of free clinical medicine papers in the Spanish sample (38.15%) is compared with the general figure and with the proportion of OA papers from Spanish authors (24.7%) in Matsubayashi et al's study, then it can be concluded that Spanish clinical articles are far more accessible than the average.…”
Section: Chronologymentioning
confidence: 75%
“…15 The second work states as its main purpose "To more completely and comprehensively capture the complex structure of OA in biomedicine." 16 While Björk and collaborators make an estimate of the scientific literature as a whole, and Matsubayashi et al 16 limit their study to the biomedical field, Altelman selects four subject categories. Her main purpose is to determine whether scholarly articles from disciplines with varying rates of OA adoption have a greater research impact if the articles are freely available online than if they are not, 17 but she also offers a detailed account of the strategies followed for achieving free diffusion of published papers.…”
Section: Institutional Repositoriesmentioning
confidence: 99%
See 2 more Smart Citations